Senior Housing as a Living Environment That Supports Well-Being in Old Age - Jolanki, Outi Hannele (Frontiers in Public Health, 2021)
Background: In different parts of the world new models of senior housing have rapidly appeared, which indicates that existing housing and care models are not fulfilling the hopes and needs of current and new generations of older people. Material and Methods: This qualitative study focuses on one type of communal senior housing complex located in a mid-sized town in Central Finland. The complex was designed to have accessible low-maintenance apartments and common spaces, and to be near easily accessible green spaces, amenities, services, and public transport. The complex has a part-time community coordinator. The minimum age limit is set at 55 years. The data consists of 36 qualitative interviews with residents (21 women, 15 men) aged 66–93, conducted between November 2018 and February 2019. The semi-structured interviews were recorded and transcribed. The data analysis focused on how different aspects of the manmade, natural, and social environment were portrayed in residents' descriptions of day-to-day life. Theoretical framework adopted for the study draws from the ideas of environmental and geographic gerontology. The data was analyzed using positioning analysis which is one form of discourse analysis. Results: The senior housing in this study fulfilled its promise of providing accessible a physical and social environment which encourages and enables residents to be physically active and independent, yet which also provides social activities and feeling safe. In this respect, the senior housing complex offered an environment which supports well-being and healthy aging. However, the residents' interpretations of what the senior housing complex represented varied. For some of the residents it was first and foremost a social place, which provided opportunities for social contacts and social activities. For some of the residents the most important were maintenance-free apartments and outdoor areas. The question remains as to how social practices, in the form of government policies and market systems can support the development of different kinds of senior housing which are affordable and accessible for all.